Parental Attitudes to Bilingual Education of Children in German-Chinese Families - Wang, Chong Jiong (International Dialogues on Education Journal, 2014)
Language is one of the major ways in which culture is manifested. One can only get inside a culture if one is able to speak, read or write in its language. The earlier one starts to learn a language, the easier it will be. In this context, children from bi-national families are not consciously learning a second language but have to face the two cultures and the two languages of their parents simultaneously and unconsciously from birth. Therefore, it would seem that children from bi-national families have the best opportunity to master the two languages. This article focuses on the way parents from ten German-Chinese families living in Germany or China deal with this issue.